2017
DOI: 10.1111/edt.12319
|View full text |Cite
|
Sign up to set email alerts
|

Shape change in mouthguard sheets during thermoforming – part 2: effect of the anteroposterior position of the model on mouthguard thickness

Abstract: The results showed that the thickness reduction was large when the distance from the model to the frame was small. This demonstrates the importance of centering the sheet and the model to achieve the most stable molding when positioning the model in the forming unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(95 citation statements)
references
References 14 publications
1
93
0
Order By: Relevance
“…Mouthguard thickness should generally be at least 3 mm to sufficiently reduce the force of impacts . However, the thickness reduction of fabricated mouthguards is remarkable as about 35%‐60% . In particular, the thickness reduction during the second stage of formation is large.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mouthguard thickness should generally be at least 3 mm to sufficiently reduce the force of impacts . However, the thickness reduction of fabricated mouthguards is remarkable as about 35%‐60% . In particular, the thickness reduction during the second stage of formation is large.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the shape change of the sheet occurs in both the first and second stages . The shape change in the first stage when the appropriate softening temperature was reached tended to increase slightly more in the central region than at the sheet periphery, and noticeable changes did not occur in the center (lowest point of the sheet sag), so the difference was only about 5% in this area.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations